The cracked reference: The intermittent speeches of chilean political documentary film - Ossa, Carlos (Re-presentaciones: Periodismo, comunicación y sociedad, 2019)
The article proposes a review of the changes in the political documentary, based on epochal turns, narrative transfigurations, modifications of optical signifiers and cultural conflicts. The basic premise is that the social is not just a content militant, but a visual form that is changing format, memory and meaning according to configurations of historical time and aesthetic ideologies